2014
DOI: 10.9755/ejfa.v26i4.16158
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional value and sanitary evaluation of raw Camels milk

Abstract: The present study was carried out to investigate the nutritional value and hygienic status of fresh camel's milk collected for a period of 12 weeks (on weekly basis). The milk samples were divided into two portions under sterile conditions. The 1 st portion was examined for the gross composition (total solids, solids non fat, moisture, fat, protein, lactose and chloride). The 2 nd portion was examined for the sanitary condition through monitoring sensory evaluation, acid value and determination of fecal contam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…As previous studies have shown, the amount of iron (about 10 times more than bovine milk) and copper in camel milk is more than bovine milk whilst some studies reported that the amount of calcium, magnesium, phosphor, sodium and potassium of camel milk is similar to bovine milk and the others reported high content of these minerals in camel milk (El-Agamy, 2006Hashim et al, 2009;Konuspayeva et al, 2011;Ahmed et al, 2014).The average ash in one-humped camel milk and bovine milk is 0.8 g/100 g and 0.7 g/100 g, respectively (Muehlhoff et al, 2013). The minimum daily requirement for calcium or phosphor is easily provided by 2.5 and 4 cups of camel milk respectively (El-Agamy, 2009).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…As previous studies have shown, the amount of iron (about 10 times more than bovine milk) and copper in camel milk is more than bovine milk whilst some studies reported that the amount of calcium, magnesium, phosphor, sodium and potassium of camel milk is similar to bovine milk and the others reported high content of these minerals in camel milk (El-Agamy, 2006Hashim et al, 2009;Konuspayeva et al, 2011;Ahmed et al, 2014).The average ash in one-humped camel milk and bovine milk is 0.8 g/100 g and 0.7 g/100 g, respectively (Muehlhoff et al, 2013). The minimum daily requirement for calcium or phosphor is easily provided by 2.5 and 4 cups of camel milk respectively (El-Agamy, 2009).…”
Section: Introductionmentioning
confidence: 94%
“…It contains health-promoting nutrients for human beings (Farah et al, 1992). Camel milk do not have allergenicity properties because it does not contains β-lactoglobulin (Mankinen & Palosuo, 1992;Ahmed et al, 2014). Recent studies revealed that camel milk has anti-diabetic property due to the presence of special protein like insulin, (Zagorski et al, 1998;Agrawal et al, 2007) as well as antioxidant and antimicrobial capacities (Salami et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The olive pomace-incorporated high fibre biscuit was subjected to sensory evaluation to measure the acceptance towards the sensory attributes of the biscuits using a fivepoint hedonic scale, where 1= dislike extremely, 2 = dislike moderately, 3 = neither like nor dislike, 4 = like moderately and 5 = like extremely according to previous reports (Gupta, Bawa, and Abu-Ghannam 2011;Ahmed, Sayed, and Sayed 2014). The sensory evaluation was carried out by 50 panelists in the age group 20 to 50 years with normal taste sensitivity and sensory evaluation experience.…”
Section: Sensory Evaluation Of Biscuitsmentioning
confidence: 99%
“…Although the overall mineral composition of camel milk has been studied, there is very little information available on the distribution of salts between the soluble and colloidal phases of camel milk as compared to caprine, ovine, bovine and buffalo milk. Camel milk has high minerals content ranged between 0.60 to 0.90% (Main mineral salts are Ca, Na, P, Mg and Cit) (Elamin and Wilcox, 1992;Konuspayeva et al, 2008 ;Ahmed et al, 2014).…”
Section: Introductionmentioning
confidence: 99%